A Look at How Regional Financial Accounting, Government Internal Control, and IT Affect Financial Statement Quality - Yaya Sonjaya; Muslim Muslim (Bata Ilyas Journal of Accounting, 2023)
This correlational study aims to explain the impact of the Regional Financial Accounting System (SAKD), the Government Internal Control System (SPIP), and the Use of Information Technology on the Quality of Regional Financial Reports at the Regional Apparatus Organization of Papua Province. The sampling technique is a Saturated sample of 67 respondents who perform duties as general treasurer/assistant/assistant, regional financial report system operator, or financial report verification section. According to the findings of this investigation, the regional financial accounting system needed to be implemented optimally. Supposedly, the implementation of the regional financial accounting system facilitates the achievement of quality regional financial management by local administrations. Implementing the regional accounting system has not optimally contributed to producing high-quality regional financial reports. The effectiveness of the government's internal control system can influence the quality of local government financial reports by continuously applying critical processes to actions and activities carried out by leaders and all employees to provide sufficient assurance of achieving organizational goals through effective and efficient workouts. Utilizing information technology in the OPD environment of the Papua Provincial Government has enhanced the role of information technology in improving the integrity of Local Government Financial Statements.Keywords:Regional Financial Accounting System, Government Internal Control System, Information Technology and Quality of Financial Statements.